Perfil criminológico del sujeto activo en los delitos de cuello blanco en el Ecuador - Vivero Torres, Johan Michel (2025)
The importance of this scientific study examines the prevalence and impact of white collar crimes in Ecuador, evaluating its effect on the economy and society, emblematic cases, legal responses and preventive measures implemented by Ecuadorian authorities are explored. The objective of this investigation is to determine the criminological profile of the active subject in white collar crimes in Ecuador, in the year 2024, this White Collar crime has particular characteristics from the profile of its author to the difficulties of the criminal process. in which it is investigated, in this work we will try to provide the reader with a thematic approach to the so-called: “White Collar Crime”, where aspects related to its genesis, evolution and approach to said criminal nature in today's society will be established, we must begin by pointing out that The genesis of the analysis of this type of criminal phenomenon is parallel to a conception of a particular State studied in greater depth.